Frankenstein makes a sandwich : and other stories you're sure to like, because they're all about monsters, and some of them are also about food, you like food, don't you? well, all right then - Rex, Adam. (Boston : Sandpiper, 2006)
Contains twenty humorous poems about the bad habits, anxieties, and other fears and foibles of monsters.
Pub Weekly
School Library Journal starred
Wilson's Children
Bulletin (Center for Children's books), September 2006
Horn Book, April 2007
Kirkus Starred, August 2006
Keywords: Children's poetry, American; Monsters -- Juvenile poetry; American poetry; Monsters -- Poetry; American poetry; Monsters -- Poetry; Picture books for children